Characterization of silver (Ag) nanomaterials, synthesized by the horizontal vapor phase crystal (HVPC) growth technique, for antimicrobial purposes - Espulgar, Wilfred V. (Animo Repository, 2010)
Triangular silver nanoplates, of different orientations, and other nanostructures were successfully synthesized for antimicrobial purposes using the Horizontal Vapor Phase Crystal (HVPC) growth technique. The starting material for the synthesis was thirty-five (35) mg of 99.99 % pure silver powder. Varied growth temperatures (800 °C, 900 °C, 1000 °C, or 1100 °C) and growth times (4 hours, 6 hours, or 8 hours) at a fixed ramp time of 80 minutes were used as parameters in this study. Scanning Electron Microscope (SEM) and Energy Dispersive X-ray (EDX) were used on the grown nanomaterials to determine the structures and the elemental composition. The SEM micrographs, which was supported by the EDX analysis, showed that nanoparticles, triangular nanoplates, hexagonal nanoplates, nanowires, nanoribbons, nanorods, and nanocubes can be grown in the HVPC technique. Analyses of the various parameters revealed that silver nanostructures are formed in all four zones of the quartz tube. Optimum size and number of nanoplates, whether triangular or hexagonal, were best grown at a low growth temperature of 800°C and a short growth time (4 hours and/or 6 hours) at zones 1 and 2. Spherical nanoparticles were best grown at the end of zones 2 and 4. The desired size can be achieved by increasing the growth time regardless of the growth temperature. Nanowires and nanorods are best grown at a high growth temperature (1100°C) and a short growth time (4 hours). Also, odd structures such as bled triangular plates, re-adsorbed particles, flakes, and forming wires were found at zones 1 and 3. Analyses of data led to the conclusion that the mechanism for deposition, nucleation, and growth of silver nanomaterials followed the vapor-solid process. Deposition of particles was affected by the growth temperature. At 800°C and 900 °C, vaporization is believed to be slow that promoted growth of 2-dimensional nanostructures. At 1000 °C and 1100°C, vaporization is believed to be fast that promoted the growth of one-dimensional nanostructures. Heterogeneous nucleation is believed to be predominantly occurred in the process since the quartz tube acted as a substrate. However, homogenous nucleation could occur when there is a decrease in saturation level brought by deposition of particles or decrease in temperature. Spectral Imaging Microscope was further used to explain why some grown nanomaterials emit different color. Real-time images of nanoparticles with spherical structure exhibited twinkling effect which was due to localized surface plasmon resonance. The pour-plate technique was employed to test the antimicrobial potency of the grown silver nanomaterials. The number of colonies grown on a plate containing silver nanomaterials, a plate containing silver powder, and a plate that do not contain silver powder were compared. Results revealed that the number of E. coli colonies grown when 105 CFU/mL of bacterial solution was exposed to a quartz tube with silver nanomaterials was decreased compared to when it was exposed to a quartz tube with or without silver powder